Knowledge and Attitudes of Mothers toward Newborn Screening Test in Baghdad City - twfeeq, Waafa Faeuq; Abed, Luma Mohammed (Diyala Journal of Medicine, 2019)
Background: The newborn screening program is a public importance health service. The early detection through newborn screening test facilitates transfer of affected infants for timely treatment, stop disabilities, and mental retardation save lives infants, families, and society, also it saves newborns from unnecessary invasive measures and families from economic and emotional costs of diagnostic odysseys, it is therefore important to highlight about newborn screening test. Objective: Determine knowledge of mothers toward concepts related to genetic testing and newborn screening test; also determine attitudes of mothers toward newborn screening test. Materials and Methods: A descriptive cross-sectional study, by used modified questioner by experts the data collection took place from the 15th December 2014 till 7th April 2015. Twenty six primary health care centers have been chosen by multi-stage random sample, with simple random sample technique to cover about 20% of all primary health care centers from AL-Karkh and Al-Russafa sectors in Baghdad city. Total study sample was 566 mothers attending primary health care centers who had children aged between 3 days -2 months. Data were analyzed through application (frequencies, percent's, mean of score (M.S.) with their standard deviation (SD), relative sufficiency (R.S.%). Results: The Results of the study show that all of the studied items were under cutoff point, since mean of score, and relative sufficiency values show a failure response, about knowledge of mothers toward concepts related to genetic testing and newborn screening test since their mean of score values, as well as relative sufficiency's values are recorded under cutoff point. The results show that all items have pass assessment of mother's attitudes toward newborn screening test. Since their means of score, and relative sufficiency's values recorded extremely upper cutoff point. Conclusion: Mother's knowledge toward concepts related to genetic testing and newborn screening test was failure. But attitudes of them toward newborn screening test were (good) passing.